Assessment of the validity and reliability of the nurses’ professional values scale—revised in Persian version among nursing students - Fahimeh Alsadat Hosseini; Ladan Zarshenas; Kobra Parvan; Maryam Shaygan; Banafsheh Tehranineshat; Brian Thomson (BMC Medical Education)
Abstract Background Evaluating professional values is crucial to developing effective strategies for integrating them into professional performance and clinical education. A standard questionnaire is an instrument that can be used to evaluate professional values. This study aimed to assess the validity and reliability of the Nurses Professional Values Scale-Revised (NPVS-R) among nursing students in the Persian language. Methods This methodological and cross-sectional study aimed to evaluate the validity and reliability of the Persian version of the NPVS-R among nursing students. Following a back-translation process, the Persian version was subjected to face, content, and construct validity assessments. Construct validity was examined using exploratory factor analysis (EFA) on a sample of 439 nursing students during their internships at 16 public universities of medical sciences in Iran between April and July 2019. Additionally, convergent and divergent validity were assessed on a separate sample of 105 nursing students. The reliability of the instrument was assessed using both internal consistency measures and the test–retest method. Furthermore, the psychometric properties of the questionnaire were analyzed using Samejima’s Gradual Response Model. Data analysis was performed using SPSS (version 19) and MPLUS (version 5.1). Results All components had a content validity ratio greater than 0.6 and a content validity index of 1, indicating excellent content validity. Exploratory factor analysis reduced the items to 25, with five factors explaining 52.26% of the variance. The scale exhibited strong convergent validity (r = 0.73, p < 0.001) and satisfactory divergent validity (r = 0.12, p = 0.21; r = 0.07, p = 0.47). Test–retest reliability was excellent, with an intraclass correlation coefficient (ICC) of 0.92. Cronbach’s alpha coefficients ranged from 0.53 to 0.83 for the factors and 0.91 for the entire scale, showing good internal consistency. IRT analysis confirmed that alpha parameters for all items were statistically significant and at an acceptable level. Thus, the Persian NPVS-R, with 25 items and 5 factors, is a valid and reliable tool for nursing students. Conclusions The Persian NPVS-R, comprising 25 items and 5 factors, demonstrated excellent validity and reliability. This scale serves as a standardized tool for evaluating the professional values of nursing students, suitable for application in educational and clinical settings to enhance nursing practice and education.